Slow human immunodeficiency virus type 1 evolution in viral reservoirs in infants treated with effective antiretroviral therapy - Persaud, Deborah; Ray, Stuart C; Kajdas, Joleen; Ahonkhai, Aima; Siberry, George K; Ferguson, Kimberly; Ziemniak, Carrie; Quinn, Thomas C; Casazza, Joseph P; Zeichner, Steven; Gange, Stephen J; Watson, Douglas C (AIDS research and human retroviruses, 2007)
A longitudinal study of viral reservoirs in children initiating highly active antiretroviral therapy (HAART) in early infancy was undertaken to test the hypothesis that early effective treatment affects the persistence of replication-competent viral latency and the evolution of HIV-1 in resting CD4(+) T cells. An end point dilution culture assay was used to measure the frequencies of latently-infected resting CD4(+) T cells harboring replication-competent virus in early and late treated children. Gag, pol, and env also were sequenced and compared to pretreatment sequences. HIV-1-specific humoral and cellular immune responses were also assessed. Blood samples were obtained from 12 HIV-1-infected children who started HAART at a median of 1.9 months of age and who maintained suppression of HIV-1 replication for up to 5.5 years. Replication-competent HIV-1 was recovered from 10/12 (84%) subjects. Evolution in gag, pol, and env was restricted for years in early-treated children. HAART initiated from early infancy does not prevent the establishment of a reservoir of latent provirus, but does significantly limit the evolution of HIV-1 in viral reservoirs. The effect of early therapy on HIV-1 evolution may have implications for long-term pharmacologic control of HIV-1.